Analisis Komunikasi Petani Kelapa Sawit Pola Swadaya di Kecamatan Bagan Sinembah Kabupaten Rokan Hilir - Nina Kirana; Roza Yulida; Yulia Andriani (Politeknik Pertanian Negeri Payakumbuh, 2021)
This research aims to determine the internal characteristics and external characteristics of the palm oil independent smallholder farmer and communication process (elements of communication) in Bagan Sinembah district, Rokan Hilir Regency. Bagan Sinembah district is a district in Rokan Hilir Regency, where the population of palm oil is cultivated. Therefore, it is necessary to analyze the characteristics of internal and external palm oil independent smallholder farmer as well as the process of communication using the survey method, selection of samples with purposive sampling methods and analysis tools Likert scale and Descriptive analysis. The results showed that the internal characteristics and external characteristics of oil palm farmers in Bagan Sinembah District, Rokan Hilir Regency are in high category (good). While the communication process in this research is seen from the elements of communication consist of extension, group chairman and management of KUD as communicator; The message is about oil palm cultivation techniques, market prices and so on which are summarized in the agribusiness system; Media used for face-to-face meetings (lectures and discussions); Farmers as communfishes; The effect of increasing knowledge, belief and behavioral change; The feedback gained is that the farmer understands with the information provided and applies the information in his venture; Physical environment namely the village hall, APKASINDO office and oil palm plantation land owned by the farmer.